Basic competency training for posyandu cadres to enhance their capacity in stunting prevention in Samarinda - Rudy Agus Riyanto; Ratih Wirapuspita Wisnuwardani; Iriyani Kamaruddin (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Stunting remains a serious public health problem in Indonesia, caused by chronic malnutrition and recurrent infections during the first 1,000 days of life. Posyandu cadres have a strategic role as the front line in promotive and preventive health services. However, many cadres still face limitations in knowledge and standard competencies related to stunting prevention. This community service activity aimed to improve the capacity of Posyandu cadres in Samarinda City through structured Basic Competency Training. The training was conducted over three days using interactive lectures, service simulations, field practices, and pre-test and post-test evaluations. A total of 60 cadres from 26 community health centers participated actively in the program. The results showed a significant improvement in participants’ knowledge scores, increasing from an average of 38.33 before the training to 78.50 after the training, as confirmed by the Wilcoxon test. In addition to improving technical knowledge and skills, the training also increased cadres’ confidence, motivation, and commitment to providing quality community services. This activity not only enhanced the cadres’ competence but also strengthened their role as agents of change in promoting healthy family nutrition behavior. Therefore, continuous mentoring and periodic refresher training are recommended to maintain the sustainability and long-term impact of the program.